Outcomes of Open, Laparoscopic, and Robotic Abdominoperineal Resections in Patients With Rectal Cancer. Issue 12 (December 2015) - Moghadamyeghaneh, Zhobin; Phelan, Michael; Smith, Brian R.; Stamos, Michael J.
Abstract : BACKGROUND: There are limited available data comparing open, laparoscopic, and robotic approaches for rectal cancer surgery. OBJECTIVE: We sought to investigate outcomes of different surgical approaches to abdominoperineal resection in patients with rectal cancer. DESIGN: The nationwide inpatient sample database was used to examine the clinical data of patients with rectal cancer who underwent elective abdominoperineal resection between 2009 and 2012 in the United States. Multivariate regression analysis was performed to compare outcomes of different surgical approaches. SETTINGS: A retrospective review according to the national inpatient sample database was designed. PATIENTS: We included patients with rectal cancer who underwent elective abdominoperineal resection between 2009 and 2012. MAIN OUTCOME MEASURES: Outcomes of different surgical approaches to abdominoperineal resection were investigated. RESULTS: We sampled 18, 359 patients with rectal cancer who underwent elective abdominoperineal resections. Of these, 69.5% had open surgery, 25.8% had laparoscopic surgery, and 4.7% had robotic surgery. The rate of robotic procedures increased >4-fold, from 2.1% to 8.1%, from 2009 to 2012. The conversion rate in robotic surgery was significantly lower compared with laparoscopic surgery (5.7% vs 13.4%; p < 0.01). After risk adjustment, patients who underwent laparoscopic and robotic approaches had lower morbidity risks compared with those who underwent the open approach (adjusted OR = 0.77 (95% CI, 0.65–0.92), 0.57 (95% CI, 0.40–0.80); p < 0. 01). There were no significant differences in the morbidity rate of patients who underwent laparoscopic or robotic approaches (adjusted OR = 0.79 (95% CI, 0.55–1.14); p = 0.21). However, patients who underwent the robotic approach had significantly higher total hospital charges compared with those who underwent the laparoscopic approach (mean difference, 24, 890; p < 0.01). LIMITATIONS: We could not adjust the results with some important factors, such as the tumor stage and BMI. CONCLUSIONS: The use of robotic and laparoscopic approaches to abdominoperineal resection have increased between 2009 and 2012. Both minimally invasive approaches decrease morbidity rates of patients undergoing abdominoperineal resection. The robotic approach has a significantly lower conversion rate compared with the laparoscopic approach. However, it had significantly higher total hospital charges compared with the laparoscopic approach.